Design of an electrochemically reactive HIV DNA biosensor by use of hairpin DNA Probes on carbon nanofibers. - Lawrenson, Nicholas (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.